Briars in the cottonpatch [videorecording (DVD)] : the story of the Koinonia farm - Fuller, Faith, 1967-; Young, Andrew, 1932- (Cotton Patch Productions, 2012)
In this tenth anniversary edition the documentary explores the events at Koinonia Farm, whose residents faced persecution and violence in the 1950s for their stand on racial equality. Compelling, heartbreaking and ultimately inspiring the roots of Habitat for Humanity.